2013
DOI: 10.1073/pnas.1315130110
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady penetration of a target by a liquid jet

Abstract: It is widely acknowledged that ceramic armor experiences an unsteady penetration response: an impacting projectile may erode on the surface of a ceramic target without substantial penetration for a significant amount of time and then suddenly start to penetrate the target. Although known for more than four decades, this phenomenon, commonly referred to as dwell, remains largely unexplained. Here, we use scaled analog experiments with a low-speed water jet and a soft, translucent target material to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Surprisingly, Lundberg's study [14] found that when the cover plate was fixed to the lateral confining tube, the effect of radial flow might be enhanced. However, only a small amount of the literature [15,16] has discussed the role of radial flow up to now. Zhai et al [17] showed that with a fixed cover plate, the DOP was reduced by 10% compared to that with a free plate, but a further explanation for this phenomenon was not provided.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, Lundberg's study [14] found that when the cover plate was fixed to the lateral confining tube, the effect of radial flow might be enhanced. However, only a small amount of the literature [15,16] has discussed the role of radial flow up to now. Zhai et al [17] showed that with a fixed cover plate, the DOP was reduced by 10% compared to that with a free plate, but a further explanation for this phenomenon was not provided.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is coupled through the fluid/structure interaction, and the rate of penetration will be affected by this coupling. Experimental investigation of this type of penetration was undertaken by Uth and Deshpande [12]. They observed that deformation of the target interface caused backflow of the jet, which then increased the force exerted on the target and thereby the penetration rate.…”
mentioning
confidence: 99%
“…Anderson Jr et al [115], based on corroborative experiments showing uncertainty interval for dwell-penetration transition velocity for borosilicate glass, stated that transition from dwell to penetration is an unstable process, analogous to BLV experiments. This unstbale process can be attributed to the unsteady fluid-structure interaction (FSI) mechanism proposed by Uth and Deshpande [114], described above.…”
Section: Backflow Of the Projectile Materialsmentioning
confidence: 92%
“…Uth and Deshpande [114] recently, conducted an experimental work, seeking the fluidstructure interaction of a liquid jet on a deformable target. They proposed and experimentally proved that impact of a jet of V 0 impact velocity, as shown in Uth and Deshpande [114] concluded that in impact of long rod heavy metal projectiles onto ceramic targets, since a depth of penetration, like δ shown in Figure 2.8 (b), into the ceramic material, is needed before establishment of the backflow of the projectile material, ceramic materials due to their brittle nature inevitably experience damage accumulation before occurrence of the backflow and unsteady penetration.…”
Section: Backflow Of the Projectile Materialsmentioning
confidence: 99%
See 1 more Smart Citation